- #1

- 27

- 0

**1. solve the following recurrence relation for an**

**2. (n+2)an+1= 2(n+1)an+2[tex]^{n}[/tex], n>=0, a0=1**

I shifted the index, multiplied through by the 2[tex]^{n}[/tex] term and then subtracted the resulting equation from the original equation to get rid of the 2[tex]^{n}[/tex] term...

**3. I have gotten to this point**

(n+1)an-4(n)an-14(n-1)an-2=0

(n+1)an-4(n)an-14(n-1)an-2=0

I'm not really sure how to handle the (n+1), n, or (n-1) terms when looking for the particular/ homogeneous solution parts.